Perception and Risk Factors Associated with Tuberculosis in the Manyara Region, Tanzania - Prudence Masanga; Sarapia Paul; Peter Mbelele; Peter Daud; Alphonce Liyoyo; Lidia Munuo; Samson Lyimo; Beatus Lyimo; Sreenidhi Srinivasan; Isabella Cattadori; Robab Katani; Vivek Kapur; et al. (Zoonotic Diseases, 2023)
Tuberculosis (TB) results from infection with members of the Mycobacterium tuberculosis complex (MTBC) and represents a major global public health concern. We here sought to assess the perceptions of human and animal TB and the prevalence of circulating MTBCs lineages and associated risk factors through a cross-sectional survey of 335 individuals presenting with symptoms of pulmonary or extrapulmonary TB in the Manyara region of Tanzania. After the enrollment of participants, a questionnaire survey was conducted, samples were collected for bacterial culture, and real-time multiplex PCR was performed to differentiate amongst primary animal and human MTBC lineages. The results show poor TB awareness: 31.6% of the participants were not aware of human TB; 82.4% were unaware of animal TB and 95.2% lacked awareness of zoonotic TB (zTB) transmission. A total of 18 recovered specimens (5%; 95% CI: 3–8%) were positive by culture, all of which were typed as M. tuberculosis sensu stricto using a lineage-specific PCR assay. While no single risk factor was significantly associated with MTBC culture positivity, the survey revealed considerable self-reported high-risk practices for contracting zTB. Together, the results show that Manyara residents have poor knowledge of diseases caused by MTBCs and high evidence of risky practices for contracting zTB.